2013
DOI: 10.1021/bi400027y
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Oligomeric Species during the Aggregation of Aβ1–40 Using 19F NMR

Abstract: In the commonly used nucleation-dependent model of protein aggregation, aggregation proceeds only after a lag phase in which the concentration of energetically unfavorable nuclei reaches a critical value. The formation of oligomeric species prior to aggregation can be difficult to detect by current spectroscopic techniques. By using real-time 19F NMR along with other techniques, we are able to show that multiple oligomeric species can be detected during the lag phase of Aβ1-40 fiber formation, consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
125
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 74 publications
6
125
0
Order By: Relevance
“…3. Conformational free energy map for the dimerization of hIAPP in terms of order parameters Q [8][9][10][11][12][13][14][15][16] and Q [27][28][29][30][31][32][33][34][35] . Contour lines are drawn every 2.5 kJ/mol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Conformational free energy map for the dimerization of hIAPP in terms of order parameters Q [8][9][10][11][12][13][14][15][16] and Q [27][28][29][30][31][32][33][34][35] . Contour lines are drawn every 2.5 kJ/mol.…”
Section: Discussionmentioning
confidence: 99%
“…Solid-state NMR (ssNMR) and X-ray crystallography provide high-resolution structures of fibrils (4,5) and optical techniques can track structural changes in real time (6,7), but few techniques have both the structural and the temporal resolution to extract specific structural details about intermediates. Fragments have been trapped in intriguing oligomeric structures that may represent intermediate states (5,8) and transient secondary structures are known to exist from circular dichroism measurements and other experiments (9)(10)(11), but for full-length proteins it has been difficult to identify the specific residues that contribute to the secondary structure and thus understand their role in the aggregation mechanism. In this paper, we use 2D infrared (2D IR) spectroscopy and isotope labeling to monitor the structural evolution of the full-length human islet amyloid polypeptide (hIAPP or amylin), a 37-residue peptide implicated in type 2 diabetes.…”
mentioning
confidence: 99%
“…Based on these H-D exchange experiments, residues that are critical for and affected by 2 binding were revealed, suggesting that this method will also be useful for understanding protein-drug interactions. 19 F NMR experiments are widely used to study ligand-protein binding and dynamics (28,29). The simplicity and high sensitivity (natural abundance of 19 F ϭ 100%) makes the application of such techniques attractive (30).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, molecular dynamics simulations showed that the Aβ (1-40) monomer transiently binds to the Aβ (1-40) oligomer by non-native contacts with the side chains before being incorporated into the fiber through native contacts with the peptide backbone [14]. Combining 19F NMR with other spectroscopic techniques, more detailed information on the secondary structure of intermediates involved in amyloid formation could be obtained [15].…”
Section: Introductionmentioning
confidence: 99%